(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This study examines the Kyrgyz and Tajik diasporas in Zomin and Yangiabad, highlighting their cultural resilience, social structures, and challenges in maintaining their identities in a new environment. Through fieldwork, interviews, and observations, the research explores how these communities preserve their traditions, language, and heritage through cultural events, language classes, and intergenerational transmission of knowledge. The close-knit social structures within the Kyrgyz and Tajik diasporas foster a sense of community and solidarity, providing support for diaspora members. However, the pressures of modernization and globalization pose challenges to the continuity of traditional practices and language use, particularly among the younger generations. The study underscores the importance of cultural revitalization efforts, intercultural dialogue, and youth empowerment initiatives to ensure the preservation and sustainability of Kyrgyz and Tajik cultural identities in Zomin and Yangiabad.